The role of quality factors on learning management systems adoption from instructors' perspectives - Abdallah, Nahel A. O.; Ahlan, Abdul Rahman; Abdullah, Odeh Abed (Association of Science, Education and Technology, 2019)
Learning management systems have been largely used in universities for teaching, student learning, curriculum, and staff development. However, just providing higher education institutions with a learning management system does not guarantee a success. Quality assurance of these systems has become a central concern for practitioners, researchers, and system providers. In this context, this empirical research investigates quality factors that can contribute to learning management system adoption. In addition, the study developed a research model based on TAM and information systems success model by integrating associated quality indicators inclusive of system quality, service quality, information quality, and instructor quality. Quantitative data using questionnaire gathered from 365 lecturers in Palestine universities were inspected to evaluate the influence of various constructs on lecturers’ adoption of learning management systems using structural equation modeling analysis technique. The research findings show that information quality, system quality, service quality, and instructors’ quality can contribute to e-learning management system adoption with regards to their beliefs. This Research contributes positively to the limited literature on assessing the quality predictors of learning management system adoption.